2018
DOI: 10.3390/nu10030377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Supplementation on Growth Outcomes in Children under 5 Years of Age

Abstract: (1) Background: The effects of zinc supplementation on child growth, and prior reviews of these studies, have shown mixed results. We aim to systematically review and meta-analyze randomized controlled trials evaluating effects of preventive zinc supplementation for 3 months or longer during pregnancy or in children up to age 5 years on pregnancy outcomes and child growth; (2) Methods: We searched PubMed, EMBASE, Cochrane Library, Web of Science, and trial registries for eligible trials up to October 10, 2017.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 31 publications
4
52
0
Order By: Relevance
“…There is also evidence that zinc supplementation can reduce the risk of respiratory infection [287,288] and pneumonia [99,288] in the same population. Recent meta-analyses of both observational data and clinical trials have shown that zinc supplementation can increase weight, height, and weight-for-age z-score in term infants [288][289][290], and that supplementation has the largest impact when begun before two years of age [289]. However, the authors conclude that multiple micronutrient supplementation is still superior to zinc supplementation alone in this age group [290].…”
Section: Zincmentioning
confidence: 98%
“…There is also evidence that zinc supplementation can reduce the risk of respiratory infection [287,288] and pneumonia [99,288] in the same population. Recent meta-analyses of both observational data and clinical trials have shown that zinc supplementation can increase weight, height, and weight-for-age z-score in term infants [288][289][290], and that supplementation has the largest impact when begun before two years of age [289]. However, the authors conclude that multiple micronutrient supplementation is still superior to zinc supplementation alone in this age group [290].…”
Section: Zincmentioning
confidence: 98%
“…Furthermore, three MAs demonstrated a reduction in incidence and duration of all-cause diarrhoea (GRADE –Moderate) ( Lazzerini & Wanzira, 2016 ; Brown et al., 2009 ; Mayo-Wilson et al., 2014 ), and one MA identified a significant reduction in mortality when used as an adjunct to treatment for severe pneumonia ( Wang & Song, 2017 ). A further four MAs noted improved, albeit across different anthropometric indices, with zinc supplementation ( Brown et al., 2009 ; Ramakrishnan, Nguyen & Martorell, 2008 ; Imdad et al., 2011 ; Liu et al., 2018 ), with more marked improvements when supplemented after two years of age ( Liu et al, 2018 ). No impacts on mental or psychomotor development were demonstrated by one MA (GRADE –Moderate) ( Gogia & Sachdev, 2012 ).…”
Section: Resultsmentioning
confidence: 98%
“…It was reported that undernourished children with serum zinc concentrations of < 750 μg/l experienced significant increase in height, weight, weight-for-age, and BMI-for-age Z-scores after 12-and 24-week zinc supplementation when compared with the children with a serum zinc concentration of ≥ 750 μg/l (Chao et al, 2018). Zinc supplementation in infants and early childhood improves specific growth outcomes, with evidence for a potentially stronger effect after 2 years of age (Liu et al, 2018). Moreover, consumption of zinc (50 mg/day for 2 months) improved the secretion of growth hormone in children aged 3.7-16.2 years.…”
Section: Discussionmentioning
confidence: 99%